2016
DOI: 10.1155/2016/5091951
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Antihypertensive Effect of Selara® (Eplerenone): Results from a Postmarketing Surveillance in Japan

Abstract: Prospective postmarketing surveillance of Selara (eplerenone), a selective mineralocorticoid receptor antagonist, was performed to confirm its safety and efficacy for hypertension treatment in Japan. The change in blood pressure after initiation of eplerenone treatment was also examined. Patients with essential hypertension who were eplerenone-naïve were recruited regardless of the use of other antihypertensive drugs. For examination of changes in blood pressure, patients were excluded if eplerenone was contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 23 publications
3
6
0
2
Order By: Relevance
“…Although the reason for this phenomenon is not clear, potential compensatory mechanisms could account for this finding, as mentioned previously . A recent postmarketing surveillance study in Japan revealed that patients with essential hypertension who received 50–100 mg of eplerenone once daily experienced a clinically significant antihypertensive effect leading to favourable blood pressure control . The results of urinary Na + /K + ratio from a single dose of eplerenone at 100 mg were almost comparable with those obtained from a single dose of esaxerenone 5 mg.…”
Section: Discussionsupporting
confidence: 58%
“…Although the reason for this phenomenon is not clear, potential compensatory mechanisms could account for this finding, as mentioned previously . A recent postmarketing surveillance study in Japan revealed that patients with essential hypertension who received 50–100 mg of eplerenone once daily experienced a clinically significant antihypertensive effect leading to favourable blood pressure control . The results of urinary Na + /K + ratio from a single dose of eplerenone at 100 mg were almost comparable with those obtained from a single dose of esaxerenone 5 mg.…”
Section: Discussionsupporting
confidence: 58%
“…Among eplerenone-naïve patients, those receiving eplerenone monotherapy accounted for 12.3%. The postmarketing surveillance (PMS) of eplerenone in Japan was conducted from May 2008 to April 2012; it revealed that among patients on eplerenone, 25.7% were on monotherapy [ 4 ]. It could be speculated that the discrepancy between the eplerenone use in the PMS and this study could be due to the differences in the patients' age.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, currently, the use of eplerenone itself is not fully delineated. Recently, the results of postmarketing surveillance of eplerenone in Japan were published [ 4 ]; the surveillance provided information on the safety and efficacy of the drug in real-world settings. Nonetheless, it did not provide detailed information on different dosages as related to patient backgrounds such as the presence of concomitant diseases including heart failure or renal disease.…”
Section: Introductionmentioning
confidence: 99%
“…Еще одно проведенное в Японии масштабное постмаркетинговое исследование, охватившее более чем 3 тысячи пациентов с АГ, получавших эплеренон в виде монотерапии или в сочетании с другими антигипертензивными препаратами в дозе 50-100 мг/сутки, подтвердило клинически значимый эффект эплеренона, позволяющий действенно контролировать АД: к 12-й неделе наблюдения среднее САД снизилось с 152,1 ± 19,0 до 134,8 ± 15,2 мм рт.ст., а среднее ДАД уменьшилось с 85,8 ± 13,7 до 77,7 ± 11,4 мм рт.ст. [5]. Общая частота побочного действия составила 2,4 %, гиперкалиемия зафиксирована у 0,6 % пациентов, головокружение и нарушение функции почек -у 0,2 % обследован-ОГЛЯД / REVIEW ных.…”
Section: огляд / Reviewunclassified
“…Закономерно, что среди главных критериев выбора средств медикаментозного лечения АГ наряду с антигипертензивным потенциалом следует рассматривать их органопротекторные свойства и способность эффективно влиять на прогноз заболевания. Этим требованиям как нельзя лучше соответствует препарат эплеренон -селективный блокатор альдостероновых рецепторов, полипотентное действие которого при кардиоваскулярной патологии, сопровождающееся досто-верным снижением АД и повышением выживаемости пациентов, а также благоприятный профиль безопасности засвидетельствованы внушительной доказательной базой [3][4][5].…”
unclassified